Helicopter interior noise reduction using compounded periodic struts. (24th November 2018) - Lu, Yang; Wang, Fengjiao; Ma, Xunjun
Abstract: This paper characterizes the performance of a novel compounded gearbox periodic strut on controlling the noise in a helicopter cabin through modelling, simulation and experimental research. The strut exhibits low transmissibility in the specified frequency ranges, called "stop bands". Based on a certain helicopter model, a dynamic acoustic-structure coupled system is first built by using the finite element method and the transfer matrix method. Subsequently, according to the gear mesh vibration transmission path, analyses of the vibration and noise reduction characteristics are conducted. Compared with the plain strut, attenuations of both vibration and noise in excess of 60 dB are obtained in the simulations. On a specially designed helicopter platform, experimental research is conducted simultaneously on the two aspects of fuselage vibration and cabin noise. The effectiveness of the novel strut used for helicopter cabin broadband noise reduction is demonstrated by the agreement between the simulation and experimentation results, where the attenuations of measured fuselage vibration and cabin noise exceed the levels of 40 dB and 30 dB, respectively, in the frequency range from 300 to 2000 Hz.